2018
DOI: 10.1007/s00134-018-5361-z
|View full text |Cite
|
Sign up to set email alerts
|

Conflicts of interest in infection prevention and control research: no smoke without fire. A narrative review

Abstract: Conflicts of interest (COIs) do occur in healthcare research, yet their impact on research in the field of infection prevention and control (IPC) is unknown. We conducted a narrative review aiming to identify examples of COIs in IPC research. In addition to well-known instances, we conducted PubMed and Google searches to identify and report case studies of COIs in IPC and antimicrobial resistance (AMR), which were chosen arbitrarily following consensus meetings, to illustrate different types of COIs. We also s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 96 publications
1
3
0
Order By: Relevance
“…On the other hand, off-label drugs that are not on the list and recommendations that are not supported by the evidence should be noticed and considered, such as infliximab for psoriasis ( Menter et al, 2020 ), which might have a possible conflict of interest. According to our analysis, more than 10% of off-label drug guidelines involve possible commercial promotion, consistent with the current situation ( Abbas et al, 2018 ).…”
Section: Discussionsupporting
confidence: 85%
“…On the other hand, off-label drugs that are not on the list and recommendations that are not supported by the evidence should be noticed and considered, such as infliximab for psoriasis ( Menter et al, 2020 ), which might have a possible conflict of interest. According to our analysis, more than 10% of off-label drug guidelines involve possible commercial promotion, consistent with the current situation ( Abbas et al, 2018 ).…”
Section: Discussionsupporting
confidence: 85%
“…2 with no statistical data) [ 123 ]. This study is also the focus of criticism because of a possible conflict of interests [ 124 ]. In the full body “wash” patient group, the incidence density of intravascular catheter-related infections caused by coagulase-negative staphylococci (CoNS), in particular, was reduced; this can also be achieved through consistent use of prevention bundles [ 65 ], [ 66 ], [ 67 ], [ 120 ].…”
Section: Recommendationsmentioning
confidence: 99%
“…In a narrative review on COIs in infection prevention and control research, Abbas et al demonstrated the all-pervasiveness of COIs, highlighting not only the relationship between industry and physicians, but also those with journal editors, guideline committee participants, and authors. They described the potentially devastating consequences of institutional COIs when these are torn between the need to report infection rates and the need to maintain a good public image, and the risk that COIs may distance guidelines from implementable practice [11].…”
Section: Can Patient Interests Be Aligned With Those Of the Doctor Ormentioning
confidence: 99%